Plan de negocios para la creación de una empresa de servicio housing para el sector de cooperativas de ahorro y crédito - Rodríguez Ángel, Julián David (2013)
This new institution will issue new requirements related to quality, security and operative continuity of the services provided by this field. Some of these requirements will be focused on mitigating operative. Cooperatives like any other business have a basic technologic infrastructure: media, computers and servers, those process and store critical information every hour; consequently a failure of these systems can affect business operations. Based on the new cooperative regulations issued by the government, a business opportunity has been identified. It focuses to provide the hosting service for main servers or backup. In order that cooperatives can operate remotely ensuring continuous service to their customers, the hosting service will be provided in an adequate place, with a security physical and electrical infrastructure, environmental control, fire protection and connectivity among other things. The development of the proposed business plan has been based on: market research, government regulations, and the extensive knowledge and expertise in the technology sector of the author of this work. The results of the financial analysis have demonstrated that the proposed service is highly profitable and attractive to investors.